The Effect of Banks and Cooperatives in Improving Welfare - Dwiputri, Inayati Nuraini; Prastiwi, Lustina Fajar; Agustin, Grisvia (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 1, Februari 2022 (pp.1-161)DO - 10.24843/JEKT.2022.v15.i01.p05, 2022)
The use of cooperative credit in Indonesia is considered one of Indonesia's supporting economies. Generally, banks in Indonesia have a lower interest rate than cooperative loans. This study wants to identify the impact of cooperative credit on public welfare compared to bank loans. This study uses Indonesian Family Life Survey (IFLS) data with a regression analysis of fixed-effect methods at the village level. The results showed that the role of cooperative and bank credit did not have a significant difference in improving people's welfare. Cooperatives have an essential role in improving people's welfare as well as the bank. The higher the amount of credit taken; the more positive effect is on improving people's welfare. The use of credit for productive purposes also has a more positive influence on improving people's welfare than consumer credit.